PTH-059 A Model Designed To Calculate The Cost Of Care For Inflammatory Bowel Disease (ibd). (9th June 2014) - Ghosh, N; Leonard, S; Miles, G; Premchand, P
Abstract : Introduction: The rising incidence of IBD, young age of onset and chronic nature mean that IBD has significant cost implications with the National IBD Audit estimating that cost to the National Health Service (NHS) exceeded £1 billion in 2010. The recent introduction of Clinical Commissioning Groups has also changed the way in which healthcare is paid for. This model is designed to be used by both commissioners and individual gastroenterology units to calculate the annual cost per patient of treating Ulcerative Colitis (UC) and Crohns Disease (CD) and to enable areas of potential cost savings to be explored. Methods: The cost of care for IBD was calculated by summing the costs of treatment, treatment side effects and disease-related complications, accounting for the proportions of patients incurring these costs. Default input values for costs, the percentage of patients receiving each treatment, and the percentage of patients experiencing side effects or complications were determined from sources such as the British National Formulary (BNF), National Institute for Clinical Excellence (NICE), NHS trusts and published literature. However, an important feature of the model was its customisability allowing users to input local data, thereby generating costs which were unique and precise for that unit. Results: Using default input values, the annual cost of treating any UC patient was estimated to be £3, 084. For a UC patient in remission, in relapse with mild-to-moderate UC or in relapse with severe UC, annual cost per patient was estimated to be £1, 693, £2, 903 and £10, 760, respectively. The annual cost for any CD patient was estimated to be £6, 156 (£1, 800 for patients in remission; £10, 513 for patients in relapse). However, inputting local data would show some variability in the costs from trust to trust. Annually £743.65 was spent per UC patient on mesalazines. The model allows exploration of the cost savings if the percentage of patients on each brand of mesalazine was altered. When the percentage of relapsing CD patients on adalimumab was increased from 5% to 10%, the annual cost per relapsing CD patient rose from £10, 513 to £11, 032. The overall annual cost for any CD patient rose from £6, 156 to £6, 416. Increasing the percentage of mild-to-moderate UC patients on leukapheresis from 0.5 to 8% increased the annual cost per mild-to-moderate patient from £2, 903 to £3, 352, and the annual cost for any UC patient from £3, 083 to £3, 263. However, assuming that increased use of leukapheresis would cause a decrease from 20% to 15% in the annual proportion of patients experiencing acute severe flares, the annual cost for any UC patient fell to £3, 078. Conclusion: This model facilitates calculation of local annual costs per UC and CD patient, and allows areas to be identified where savings could be made. Disclosure of Interest: None Declared.